Study of plasma spray aluminum conditions under microwave oven driven on coating characteristics - Muhammad Fahmi Izuwan, Samion (2022)
The plasma spraying method is the most versatile coating technique for depositing high melting point materials such as ceramics and cermets, used for wear, corrosion, and heat resistance purposes. It uses a heat source generated by direct current, radio frequency, or microwave as the power source to melt the spray particles injected either axially or radially inside the plasma plume. The microwave oven-induced plasma method is a novel application of the microwave oven to generate plasma for the coating process. It uses 2.45 GHz microwave power and only 0.8 kW input power to produce the plasma capable of depositing all sprayable materials for coating. However, more research regarding this microwave plasma spray is needed to be discovered. A suitable plasma torch with laminar flow is needed to produce the desired microwave-generated plasma for coating application. Our research group generated the plasma with a microwave oven and succeeded in fabricating an aluminum coating. However, the mechanism and characteristics of the process are not studied well yet. Thus, the main objective of this research is to study the operational characteristics of the microwave oven-driven plasma spray method. Moreover, the improvements and renovation of the spray device are also studied and presented. A microwave oven-driven plasma spray device was designed and developed for thermal spray application. In this objective, we learn to optimize how to produce acceptable plasma for coating application. Many factors need to be addressed for this design; one of them is the ignition condition which led to Reynold's number calculation. From our experiment, all outer diameter of the antenna is below 2000, which indicates laminar flow. The plasma shows more stable discharge when laminar flow occurs rather than turbulence. The microwave plasma can be generated and stabilized using our designed microwave oven as a result of the plasma ignition study. Argon gas is a working gas to produce plasma for our device. During ignition study, several designs are tested, and many factors are considered to affect our microwave device. From our observation, the presence of a waveguide is significant in helping plasma production; using an 8 mm gap between the tip of the antenna and a 13 mm window diameter results in the thermal pinching effect, which plays a vital role in this design experiment process. For the coating deposited using microwave oven-driven plasma spray device evaluation, aluminum powder coating onto stainless steel SUS304 substrate was successfully deposited. Based on the result, a higher working gas flow rate will produce a more fine coating. With the decrease of spray distance, more melted particles are being impinged and less dispersed on the surface of the substrate. In conclusion, this microwave oven-driven plasma spray is able to produce a stable plasma with adequate power to deposit coating. Future research should be conducted to improve some of its features towards realizing this method in the mainstream thermal spray technique.